Engineering Performance: The Role Of Knowledge Sharing Teams In A Malaysian Manufacturing Firm - Ng, Poh Kiat; Jee, Kian Siong (Journal of Knowledge Management Practice, 2011)
In most manufacturing industries, knowledge sharing teams accentuate the importance in cultivating knowledge sharing initiatives which would eventually lead to improved project performance. To understand this contribution factor, this study is conducted to examine the effects of knowledge sharing teams (which comprise of quality teamwork and cross-functional teamwork) on engineering performance in a Malaysian manufacturing firm. In this study, semi-structured interviews and surveys are conducted to gather qualitative and quantitative evidence. Our findings suggest that there is a significant and positive relationship between knowledge sharing teams and engineering performance. The findings also suggest that 44.8% of the variance in engineering performance is explained by quality and cross-functional teamwork. However, it is observed that there are barriers in interdepartmental collaborations when it comes to cross-functional teamwork. From our findings, we conclude that this is possibly due to the nature of the industry which consists of long and complex process flows. Thus, a possible solution would be to form a specific project group which could eliminate barriers in knowledge sharing among team members and cultivate cross-functional teamwork.